A multi spin echo pulse sequence with optimized excitation pulses and a 3D cone readout for hyperpolarized 13C imaging. Issue 4 (15th March 2020) - Somai, Vencel; Wright, Alan J.; Fala, Maria; Hesse, Friederike; Brindle, Kevin M.
Abstract : Purpose: Imaging tumor metabolism in vivo using hyperpolarized [1‐ 13 C]pyruvate is a promising technique for detecting disease, monitoring disease progression, and assessing treatment response. However, the transient nature of the hyperpolarization and its depletion following excitation limits the available time for imaging. We describe here a single‐shot multi spin echo sequence, which improves on previously reported sequences, with a shorter readout time, isotropic point spread function (PSF), and better signal‐to‐noise ratio. Methods: The sequence uses numerically optimized spectrally selective excitation pulses set to the resonant frequencies of pyruvate and lactate and a hyperbolic secant adiabatic refocusing pulse, all applied in the absence of slice selection gradients. The excitation pulses were designed to be resistant to the effects of B0 and B1 field inhomogeneity. The gradient readout uses a 3D cone trajectory composed of 13 cones, all fully refocused and distributed among 7 spin echoes. The maximal gradient amplitude and slew rate were set to 4 G/cm and 20 G/cm/ms, respectively, to demonstrate the feasibility of clinical translation. Results: The pulse sequence gave an isotropic PSF of 2.8 mm. The excitation profiles of the optimized pulses closely matched simulations and a 46.10 ± 0.04% gain in image SNR was observed compared to a conventional Shinnar–Le Roux excitation pulse. The sequence was demonstrated with dynamic imaging of hyperpolarized [1‐ 13 C]pyruvate and [1‐ 13 C]lactate in vivo. Conclusion: The pulse sequence was capable of dynamic imaging of hyperpolarized 13 C labeled metabolites in vivo with relatively high spatial and temporal resolution and immunity to system imperfections.